1989
DOI: 10.1128/jb.171.2.799-806.1989
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific recombination at oriT of plasmid R1162 in the absence of conjugative transfer

Abstract: R1162 is efficiently comobilized during conjugative transfer of the self-transmissible plasmid R751. Bacteriophage M13 derivatives that contain two directly repeated copies of oriT, the site on R1162 DNA required in cis for mobilization, were constructed. Phage DNA molecules underwent recombination during infection of Escherichia coli, with the product retaining a single functional copy of oriT. Recombination was strand specific and depended on R1162 gene products involved in mobilization, but did not require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…Two simultaneous C-to-T transitions at bp 30 and 32 ( Fig. 1, line 2) affect the initiation of transfer but not the termination step modeled by the recombination of oniT copies in M13 (10,14). Deletion of bp 1 to 8, which make up the outer arm of the inverted repeat in oriT ( Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two simultaneous C-to-T transitions at bp 30 and 32 ( Fig. 1, line 2) affect the initiation of transfer but not the termination step modeled by the recombination of oniT copies in M13 (10,14). Deletion of bp 1 to 8, which make up the outer arm of the inverted repeat in oriT ( Fig.…”
mentioning
confidence: 99%
“…RSF1010 DNA has been isolated as a relaxosome (16); more recently, this complex has been reconstructed from plasmid DNA and purified proteins (18). The recircularization of plasmid DNA after transfer is modeled by the recombination of directly repeated oriT copies on replicating M13 phage DNA (1,14). In this system of recombination, it is likely that the singlestranded oriT copies are treated as intermediates in transfer and are therefore cleaved and ligated at the nic site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recombination between oriTs on single-stranded M13 phage is a measure of the single-strand cleavage and rejoining activity of MobA (23). We found that a MobA amino-terminal fragment extending to residue 179 in MobA was inactive in recombination, whereas a fragment extending to residue 204 was fully active (pUT208 and pUT209 in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…An oriT mutation which inhibits nicking in the relaxosome has no effect on the termination of transfer at a second oriT (Kim and Meyer, 1989). In addition, oriTs cloned into single-stranded M13 phage DNA can undergo site-specific recombination at the normal cleavage site (Meyer, 1989). This reaction requires the relaxase, but not the other components of the relaxosome.…”
Section: Electroporation and Matingmentioning
confidence: 99%